Hodnocení finanční situace vybrané soukromoprávní korporace metodami finanční analýzy a návrhy na její zlepšení - Cícha, Marek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce se zabývá hodnocením finanční situace společnosti TVD – Technická výroba, a.s. na základě účetních výkazů za období 2016–2020 a návrhy na zlepšení této finanční situace. Práce je rozdělena do dvou částí, a to na teoretickou a analytickou. Teoretická část vymezuje základní pojmy, které jsou nezbytné pro zpracování práce. Analytická část obsahuje představení analyzované společnosti, analýzu současného stavu společnosti a návrhy na zlepšení její finanční situace.

The bachelor thesis deals with the evaluation of the financial situation of the company TVD – Technická výroba, a.s. which is based on the financial statements for the period of 2016-2020 and proposals for improvement of this financial situation. The work is divided into two parts, theoretical and analytical. The theoretical part defines the basic concepts that are necessary for the processing of work. The analytical part contains an introduction to the analyzed company, an analysis of the current state of the company and suggestions for improving its financial situation.
Evaluation of the Economic Situation of the Selected Private Corporation and Proposals to its Improvement
Keywords: finanční analýza; rozvaha; výkaz zisku a ztráty; SWOT analýza; produktivita; rentabilita; likvidita; cash flow; financial analysis; balance sheet; profit and loss statement; SWOT analysis; productivity; profitability; liquidity; cash flow